Metody zwiększania frekwencji wyborczej. Polska a doświadczenia innych państw - Musiał-Karg, Magdalena (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
Numerous reports and analyses of voter turnout levels have recorded the global trend of declining participation by citizens in national elections. One of the most important results of poor participation of citizens in electoral processes is the serious legitimization deficit. Governments in many countries try to prevent that by taking various measures to solve the problem of falling turnout and to increase the level of the electorate’s involvement. In Poland, the low turnout level has been the subject of many scholarly discussions aimed at finding solutions to the problem of poor civic participation. The main goal of this study is to assess the various methods of increasing voter turnout which are used in different countries, including Poland.